Oral adjuvanted Vibrio vaccine enhances antibody production and lysozyme activity in the serum and mucus of marine-cultured red hybrid tilapia (Oreochromis sp.) against V. harveyi and V. alginolyticus - Manchanayake, Tilusha; Mohamad, Aslah; Amir-Danial, Zahaludin; Abu Nor, Nadirah; Yong-Kit, Chin; Nazarudin, Muhammad Farhan; Md Nor, Roslindawani; Hasnan, Qistina; Zamri-Saad, Mohd; Azmai Amal, Mohammad Noor; Ina-Salwany, Md Yasin; Salleh, Annas (Academic Press, 2025)
Vibriosis, caused by Vibrio species, is a significant issue in marine aquaculture. Vibrio species such as Vibrio harveyi, V. alginolyticus, and V. vulnificus threaten fish health, and the use of antibiotics raises public health concerns, highlighting the need for vaccination. This study explores a formalin-killed feed-based vaccine against V. harveyi, with an oil adjuvant to boost immune responses in marine-cultured red hybrid tilapia (Oreochromis sp.), aiming for cross-protection against various Vibrio species. A total of 450 red hybrid tilapia were divided into three groups: oil-adjuvanted vaccine feed, non-adjuvanted vaccine feed, and control feed. Immune responses in the mucus and serum, indicated by IgM levels and lysozyme activity, were assessed following oral vaccination at weeks 0, 2, and 6 over a 16-week period. Vaccinated fish exhibited significantly higher IgM levels in both mucus and serum against V. harveyi and V. alginolyticus, with oil-adjuvanted vaccine feed group showing peak mucus IgM of 0.47 ± 0.05 OD at week 8 for V. harveyi and consistently higher levels than unvaccinated control group for both Vibrio species from weeks 4–16 (p < 0.05). Similarly, lysozyme activity in the oil-adjuvanted vaccine feed group was significantly elevated, with peak values of 80.83 ± 17.03 U/mg in mucus and 204.27 ± 32.27 U/mg in serum at week 4, higher than the non-adjuvanted and unvaccinated groups across the study period (p < 0.05). The oil-adjuvanted oral Vibrio vaccine significantly enhanced IgM antibody levels and lysozyme activity in both serum and mucus of red hybrid tilapia, indicating strong mucosal and systemic immune responses against V. harveyi and V. alginolyticus. The oral delivery and cross-protective effects of this vaccine support its suitability for farm-level vaccination programs, aiming to reduce antibiotic use and enhance fish health management.